Prevalence and knowledge of gastroesophageal reflux in young people (Jóvenes en la Ciencia, 2024)
Various investigations have shown that Gastroesophageal Reflux Disease (GERD) is a global disease whose prevalence is increasing. Therefore, the high prevalence of GERD and its associated symptoms has important consequences in society since it negatively impacts work productivity. Objective: Identify the knowledge and prevalence of gastroesophageal reflux in young people. The Gastroesophageal Reflux Disease Questionnaire (GERDQ) was used to identify symptomatology in young people and the GERD knowledge questionnaire. A population of 101 young people was selected in the range of 18 to 24 years old, who were chosen as a matter of convenience from the Irapuato municipality, from different universities such as “Escuela Normal Oficial De Irapuato” (ENOI), “Instituto Tecnológico Superior de Irapuato” (ITESI) and “Universidad de Guanajuato” (UG). A percentage of 90% was obtained in sufficient knowledge of GERD and 68% of students did not present symptoms. These results suggest that there is a high knowledge about the pathology and, therefore, there is a low prevalence.